Relationship Between Parent's Attention with the Independency of Drop-Out Teenagers in Nagari Pulai Mainan, Kabupaten Dharmasraya - Puja Intan Cahyati; Solfema Solfema (Universitas Negeri Padang, 2022)
This research is motivated by the low level of independence of out-of-school teenagers in Nagari Pulau Mainan, Dharmasraya Regency, this is presumably because parents' attention to the independence of dropout teenagers is low. The objectives of the study are as follows: 1) to find out how high the level of parental attention is to teenagers dropping out of school at the junior high school level in Nagari Pulau Mainan, Dharmasraya Regency; 2) to determine the level of independence of junior high school dropouts in Nagari Pulau Mainan, Dharmasraya Regency; 3) to find out whether there is a relationship between parental attention and the independence of junior high school dropouts in Nagari Pulau Mainan, Dharmasraya Regency. This research uses quantitative research and correlational descriptive technique. The population of this study were 24 students who dropped out of school in Nagari Pulau Mainan, Dharmasraya Regency and a sample of 18 people. Collecting data in this study using a questionnaire and to analyze the data using a statistical formula, namely the percentage formula and Spearman rho to determine whether or not there is a relationship between two variables. After the data is processed, the results obtained are: (1) parental attention to the independence of low school dropout teenagers, (2) low independence of dropout teenagers, (3) data obtained showing that there is a significant relationship between parental attention and independence dropout teenagers in Nagari Pulau Mainan, Dharmasraya Regency. It is recommended that parents increase parental attention to the independence of out-of-school teenagers so that teenagers can be more independentKeywords: perhatian orangtua, kemandirian remaja putus sekolah